Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and diffusion-weighted imaging of bone marrow in healthy individuals - Hillengaß, Jens; Stieltjes, Bram; Bäuerle, Tobias; McClanahan, Fabienne; Heiß, Christiane; Hielscher, Thomas; Wagner-Gund, Barbara; Habetler, Verena; Goldschmidt, Hartmut; Schlemmer, Heinz-Peter; Delorme, Stefan; Zechmann, Christian (Acta radiologica, 2011)
BackgroundDynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) displays microcirculation and permeability by application of contrast-media and diffusion-weighted imaging (DWI) is a tool for quantification of cellularity in the investigated area. Recently published examples cover breast cancer, CNS tumors, head and neck cancer, gastrointestinal cancer, prostate cancer as well as hematologic malignancies.PurposeTo investigated the influence of age, sex, and localization of the investigated region on findings of DCE-MRI and DWI.Material and MethodsDCE-MRI-parameters amplitude A and exchange rate constant kep as well as the DWI-parameter ADC of the bone marrow of the lumbar vertebral column of 30 healthy individuals covering the typical range of age of tumor patients were evaluated. ADC was calculated using b=0 and a maximal b value of either 400 or 750 s/mm2.ResultsAmplitude A of DCE-MRI decreased with age (P = 0.01) and amplitude A, exchange rate constant kep as well as ADC based on b = 400 s/mm2 and b = 750 s/mm2, respectively, decreased significantly from the first to the fifth lumbar vertebra with P = 0.02, P = 0.05, P = 0.003, and P = 0.002, respectively.ConclusionQuantitative parameters of functional imaging techniques in bone marrow are influenced by the age of the examined individual and the anatomical location of the investigated region.
Gesehen am 14.09.2022